Effects of Nested Interruptions on Task Resumption: A Laboratory Study With Intensive Care Nurses. (June 2017) - Sasangohar, Farzan; Donmez, Birsen; Easty, Anthony C.; Trbovich, Patricia L.
Objective: Interruptions to secondary tasks resulting in multiple tasks to resume may tax working memory. The objective of this research is to study such interruptions experienced by intensive care unit (ICU) nurses. Background: ICU nurses are frequently interrupted, resulting in a switch from primary to secondary tasks. In two recent studies, we observed that some of these secondary tasks also get interrupted, resulting in multiple tasks that have to be resumed, a phenomenon we refer to as nested interruptions. Although completing multiple secondary tasks in a serial fashion during an interruption period can create context-switching costs, we hypothesize that nested interruptions tax the working memory even more than just performing multiple secondary tasks sequentially because the nurse would have to encode in working memory the resumption goals for both the primary and the interrupted secondary tasks. Method: We conducted a laboratory study with 30 ICU nurses, who performed an electronic order-entry task under three interruption conditions: (a) baseline—no secondary task during the interruption period; (2) serial—performance of two tasks one after the other during the interruption period; and (3) nested—performance of two tasks during the interruption period, one of which was also interrupted. Results: Nested interruptions resulted in significantly longer primary-task resumption lag and less accurate task resumption compared with both the serial interruption and baseline conditions. Conclusion: The nested nature of interruptions adds to the resumption lag and diminishes resumption accuracy by likely populating the working memory with goals associated with interrupted secondary tasks.